Knowledge, attitude and practices towards safety culture and its associated factors among staff of a public university, Malaysia - Oluwaseun, Odu Josiah (2018)
Workers practicing good work safety culture (WSC) will have less accidents at their workplace. This principle applies in public institution such as in Universiti Putra Malaysia (UPM). Work safety culture is usually studied in the dangerous sectors, but published articles on work safety culture among staff of the university setting in Malaysia is scarce. The main objective of this study was to determine the proportion and predictors of knowledge, attitudes and practice (KAP) on work safety culture (WSC) among staff of Universiti Putra Malaysia (UPM). A cross-sectional study was conducted on 220 randomly selected employees who had been working for at least one year among the staff of Universiti Putra Malaysia. The self-administered questionnaire was used to collect information on socio-demographic, employment characteristics, as well as data on knowledge, attitudes and practice towards work safety culture. Data were analyzed by using the IBM Statistical Package of Social Sciences (SPSS) version 22. The results of the study showed that out of 184 respondents who answered the questionnaire 174 (94.6%) had good knowledge on safety culture, 128 (69.6%) had positive attitudes towards safety culture and 140 (76.1%) had good practice towards safety culture. Chi square test showed factors that were significantly associated with KAP of safety culture: employment status (p=0.031) with knowledge on safety culture, work duration (p=0.036), educational level (p=0.020) and marital status (p=0.051) with attitudes towards safety culture and gender (p=0.039), employment status (p=0.053) with practice towards safety culture. Binary logistic regression test showed the significant predictor factors to KAP of safety culture were employment status (OR=1.19, 95% CI:1.09-5.70) with knowledge on safety culture, work duration (OR=1.51, 95% CI: 1.25-6.07), educational level (OR=1.29, 95% CI: 1.19-5.82), marital status (OR=1.07, 95% CI: 1.02-5.38) with attitudes towards safety culture and gender (OR=1.92, 95% CI: 1.45- 6.91) with practice towards safety culture. This study reports that good knowledge, positive attitude and good practice of safety culture was prevalent among the staff of UPM but still lower compared to those found in other studies on safety culture, most especially the attitude of the staff towards work safety culture. Those come from higher education background, higher working experience and single are associated with lower odds of positive attitude towards safety culture and the male staff are as well associated with lower odds of good practice towards safety culture. Hence, in creating awareness on work safety culture in other to minimize work related injury and improve work safety performance, researches on safety culture among staff in the academic setting should be more alert, and to identify staff with higher education background, higher working experience and single as such staff are more likely to have lower positive attitude towards safety culture and male staff as well are more likely to have lower good practice towards safety culture at work.